COKELAT HITAM SEBAGAI MAKANAN KAYA NITRIC OXIDE UNTUK MENANGGULANGI COVID-19: SYSTEMATIC REVIEW: Dark Chocolate and Its Preventive Effect from Covid-19 - Abdul Rohim Tualeka; Zulfa Anida; Ahmad Ridoi Yuda Prayogi; Juliana Jalaludin; Syamsiar S Russeng; Ahsan Ahsan; Indri H Susilowati; Pudji Rahmawati; Ayik Mirayanti Mandagi (Faculty of Public Health, Andalas University, 2022)
Coronavirus 19 is a deadly disease that can kill thousands of people worldwide. However, not many researchers know that NO content can kill the COVID-19 virus. This research method is study design used retrospective methods, prospective and a systematic review. Search for reference sources began on March 10th - June 1st, 2021, using several online databases: 1) Pubmed, 2) Science Direct, 3) Google Scholar. Keywords used in the search term: COVID-19, Novel Coronavirus, SARS-CoV, Nitric Oxide, Dark Chocolate, Macrophages and included in journals accredited. This study looked for a list of references from the study, including 103 studies taken through the search. There are 63 articles in cleaning, and eight articles are included in the discussion. This review shows that COVID-19 can be attenuated and killed by the NO content produced by macrophages and supplied with NO content modulated by dark chocolate. Modulating NO-rich foods such as dark chocolate can effectively kill COVID-19. NO can also cure several diseases such as high blood pressure, diabetes, cardiovascular disease, and some respiratory infections.